Pengaruh Kemampuan Koneksi Dan Komunikasi Matematis Melalui Model Pembelajaran Cooperative Tipe STAD Terhadap Pemahaman Matematis Siswa - Cahyani, Yeni Indah Wahyu; Hatip, Ahmad; Muhajir, Muhajir (Universitas Batanghari Jambi, 2022)
This research is a descriptive and quantitative research. The purpose of this study was to determine the effect of mathematical connection and communication skills through the STAD type cooperative learning model on the mathematical understanding of students in class VIII-J of SMP Negeri 30 Surabaya. This population is all eighth grade students of SMP Negeri 30 Surabaya for the 2018/2019 academic year. The sampling technique was done by simple random sampling. The research sample was all students of class VIII-J of SMP Negeri 30 Surabaya as many as 35 students. The instruments used are questionnaires and tests about explanations. The data obtained were analyzed or tested for hypotheses using simple linear regression and multiple linear regression. The results of the study are (1) There is an effect of mathematical connection ability on students' mathematical understanding ability. If students have high connection skills, then the ability to understand mathematics is also high. (2) There is an effect of mathematical communication skills on students' mathematical understanding abilities. If students have high communication skills, then the ability to understand mathematics is also high. (3) There is an influence between connection ability and communication ability on students' mathematical understanding. when tested simultaneously, these connection skills and communication skills have a significant effect on students' mathematical understanding.